1997
DOI: 10.1038/bjc.1997.160
|View full text |Cite
|
Sign up to set email alerts
|

Body weight and vascular invasion in post-menopausal women with breast cancer

Abstract: Summary To examine the relationship between body weight and vascular invasion (VI) around tumours in post-menopausal women with operable breast cancer, a retrospective study was conducted of 393 patients treated in a breast unit between 1987 and 1991. Weight was measured at the time of diagnosis. Vascular invasion was recorded as being present or absent. Vascular invasion was seen in slightly more of the 50 perimenopausal patients than in the 343 post-menopausal women (44% vs 36%). In the tumour specimens from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
2

Year Published

1999
1999
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 29 publications
0
7
2
Order By: Relevance
“…29,30 In contrast to other studies demonstrating higher rates of triple-negative breast cancer, 1921 the heavy patients in our sample were less likely to have triple-negative tumors. Obese women in our sample, as in others, 32 are more likely to have diabetes.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…29,30 In contrast to other studies demonstrating higher rates of triple-negative breast cancer, 1921 the heavy patients in our sample were less likely to have triple-negative tumors. Obese women in our sample, as in others, 32 are more likely to have diabetes.…”
Section: Discussioncontrasting
confidence: 99%
“…In logistic regression, angiolymphatic invasion was independently associated with nodal status, histologic grade, weight, and height. 29 The investigators did not, however, control for other factors associated with tumor biology, such as estrogen receptor status or diabetes. Information on the presence or absence of angiolymphatic invasion is largely missing from studies of breast cancer prognosis in obese women.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of unopposed estrogen in breast cancer was shown in another study from Guy's (28). Postmenopausal fatter women tend to have higher levels of circulating estrogen because of aromatization of adrenal androgens in the adipose tissue.…”
Section: Clinical and Laboratory Trialsmentioning
confidence: 83%
“…Further reduction in the cohesion of malignant cells during the ‘‘unfavorable’’ time of the menstrual cycle and increased exfoliation has also been reported (3,42). In an environment of unopposed estrogen, such as in obese postmenopausal women, vascular invasion was more frequently observed and was associated with a worse survival (28). The histologic finding of vascular invasion may be a ‘‘snapshot’’ of tumor cells invading systemic or lymphatic circulation as a result of the pressure exerted on the cancer during surgery.…”
Section: Pathophysiological Rationalementioning
confidence: 99%
“…[32]. A study of 393 postmenopausal patients at Guy's Hospital (London, UK) showed a direct relationship between LVI and BMI [33]. In the specimens from those <50 kg, LVI was observed in 11% compared with 45% from women >80 kg (p = 0.02).…”
Section: Aromatasementioning
confidence: 99%